A genome-wide integrated analysis of lncRNA-mRNA in melanocytes from white and brown skin hair boer goats (Capra aegagrus hircus) - Kai-yuan, Ji; Yi-Wei, Zhao; Ru-jun, Wen; Khan, Ibrar Muhammad; Yun-hai, Zhang (Frontiers in Veterinary Science, 2022)
Long non-coding RNAs (lncRNAs) are involved in many biological processes and has been extensively researched. Nonetheless, literature focusing on the roles of lncRNA in melanocytes is limited. Melanocytes are located in the basal layer of epidermis, and determine the color of an animal's skin and hair by producing melanin. The mechanisms of melanogenesis remain unclear. Herein, melanocytes from Boer goat skins were successfully isolated and verified using morphological observation, dopamine staining, silver ammonia staining, and immunohistochemical staining in vitro. Phenotypic testing revealed that melanocytes isolated from goat skins with white and brown hair showed significant differences in proliferation, migration, and melanogenesis (**P < 0.01). RNA sequencing was performed with the isolated melanocytes, and through bioinformatic analysis, several candidate lncRNAs and mRNAs involved in stage-specific melanogenesis were identified. Functional enrichment analysis indicated that miRNA precursors and cis-regulatory effects of lncRNAs were deeply dissected using function prediction software. Multiple lncRNA–mRNA networks were presumed to be involved in melanocyte migration, proliferation and melanogenesis based on Kyoto Encyclopedia of Genes and Genomes (KEGG) annotation. This research provided novel bioinformatic insights into the roles of lncRNAs in mammalian pigmentation.